Case Report: Mepolizumab in the treatment of idiopathic chronic eosinophilic pneumonia [version 3; peer review: 2 approved] - Moetemri Zied; Samira Mhamdi; Ghedira Hela; Aida Ayadi; Selsabil Daboussi; Samia Essebaa; Chiraz Aichaouia (F1000Research, 2023)
Idiopathic chronic eosinophilic pneumonia (ICEP) is a rare interstitial lung disease of unknown cause. It usually responds well to systemic corticosteroid therapy, but relapses are frequent. We describe two cases of 21- and 27-year-old patients, presenting with dyspnea. The diagnosis of steroid-relapsing and steroid-dependent ICEP was made respectively. Mepolizumab was prescribed to both patients. This treatment resulted in successful long-term disease management with much fewer side effects than a traditional corticosteroid therapy.